Clinical outcomes of intracranial complications secondary to acute mastoiditis: The Alder Hey experience. (January 2020) - Krishnan, Madhan; Walijee, Hussein; Jesurasa, Anthony; De, Su; Sinha, Ajay; Sharma, Ravi; Donne, Adam
Abstract: Objective: Acute mastoiditis is the most common intra-temporal complication of acute otitis media. Its management remains a challenge due to potential extracranial and intracranial complications. This study was designed to evaluate the recent experience with acute mastoiditis and its associated intracranial complications at a tertiary paediatric centre. Methods: A retrospective case note review was carried out for patients admitted to Alder Hey Children's Hospital between January 2006 and December 2016 with a diagnosis of acute mastoiditis. Patients were identified using ICD-10 codes H700, H701, H702, H708 and H709. A case note review was performed to identify patients with intracranial complications and data collected. Results: 30 patients were identified with intracranial complications of acute mastoiditis, with 18 males and 12 females. The average age was 4 years and 2 months (range 2 months–15 years). The most common presenting complaint was otalgia and vomiting (63%), with only 27% patients presenting with mastoid swelling. 83% of patients were investigated with a combination of CT and MRI scans, 6.7% with CT scans only and 6.7% with MRI scans only. 73% were diagnosed with sinus thrombosis, 40% cerebral abscess and 33% postauricular subperiosteal abscess. 78% of the patients required surgical intervention. 27 of the 30 patients recovered fully with no significant long term sequalae following an average of 50 months follow-up. Conclusion: Intracranial complications of acute mastoiditis remain a significant challenge. Most patients tend to present without mastoid swelling, necessitating a high index of suspicion in patients with picket fence fever, vomiting, drowsiness, headaches, seizures or cranial nerve involvement. Most cases treated at our institution required acute surgical intervention in addition to adjuvant medical treatment with majority patients recovering fully.